Experience of integrating web 2.0 technologies - Zdravkova, Katerina; Ivanović, Mirjana; Putnik, Zoran (Springer US, 2012)
Web users in the 21st century are no longer only passive consumers. On a contrary, they are active contributors willing to obtain, share and evolve information. In this paper we report our experience regarding the implementation of Web 2.0 concept in several Computer Ethics related courses jointly conducted at two Universities. These courses have been delivered to undergraduate and graduate students. The paper addresses main deficiencies of traditional E-learning noticed in earlier years and offers an alternative approach based on social media and collaborative creation of joint contents. Each Web 2.0 feature directly implemented in our courses is presented in details. Particular attention is paid to workload, student feedback and to observed benefits and disadvantages.
Keywords: Social networks Collaborative content creation E-learning Publishing technologies